FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT LAPORAN KEUANGAN PEMERINTAH - Challen, Auliffi Ermian; Aryani, Amelia Dwi (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2021)
Many problems in managing state finances necessitate quality audited financial statements. Quality audits must also be carried out to maintain public trust in The Audit Board for its roles in conducting the audits of the management and responsibility of state finances. This study examines the factors that influence the audit quality of the government’s financial statements, namely independence, competence, integrity, auditor ethics, objectivity, and motivation. The population in this study were auditors of The Audit Board of the Republic of Indonesia (BPK RI) Head Office. The number of samples in this study reached 70 respondents. The research method used is quantitative, with primary data analyzed using multiple regression. The study results showed that independence, competence, integrity, auditor ethics, objectivity, and motivation positively affect the audit quality of the government’s financial statements.